Influence of Cognitive, Affective, and Conative Elements in Promoting Engineering Problem Solving Skills - Omar, Norasyikin; Mohamad, Mimi Mohaffyza; Ibrahim Mukhtar, Marina; Paimin, Aini Nazura (Journal of Technical Education and Training, 2019)
Problem solving is one of the main challenges that needs to be mastered in engineering learning. This study aimed at looking whether cognitive, affective and conative elements play role in the process of mastering problem solving skills in engineering learning. Cognitive, affective and conative refer to the â€˜Trilogy of Mindâ€™ concept. Educational innovation from 1980-2016 shows that elements proposed in the â€˜Trilogy of Mindâ€™ capable in improving academic achievement. Previous studies conducted among engineering students in polytechnics Malaysia show the importance of cognitive, affective and conative elements in mastering problem solving in learning. This study continued in the process of looking whether cognitive, affective and conative can enhance the engineering learning. Strategy (cognitive), attitude (affective) and initiative (conative) are elements that are found to be able to improve academic achievement through the mastery of problem solving. An in-depth study is referring to the process of looking the relationship between strategy and attitude, initiative and attitude as well as the strategy and initiative. This study uses a survey design with a quantitative approach. The sampling method used is a simple random technique. A total of 100 engineering students from polytechnics were involved in this study. The data is analysed based on inferential statistic. The results showed that planned strategy in problems solving can be influenced by students’ attitudes. Besides that, student attitude contributes to student initiative level. Strategy is also associated with initiative in mastering problem solving.